If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + -8 = 15 Reorder the terms: -8 + 2t = 15 Solving -8 + 2t = 15 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 2t = 15 + 8 Combine like terms: -8 + 8 = 0 0 + 2t = 15 + 8 2t = 15 + 8 Combine like terms: 15 + 8 = 23 2t = 23 Divide each side by '2'. t = 11.5 Simplifying t = 11.5
| 2(x-2)+10(x+9)= | | 6x-5=13x+33 | | x^3=19x+30 | | 10v=-2 | | y=20+20x | | -10=s-(-6) | | 4log(4x)=12 | | X+17=204 | | 7s=-9 | | y=3x+-3 | | 10x-9=2x+11 | | (-3ln+6lnx)=6 | | 36*x^4=4.5 | | -5y+x=-3 | | x^2+0.106x-0.106=0 | | 9(x+2)=7x+25 | | 24=60-8x | | s-(-10)=2 | | 24=60-x | | 3x+12=6x+5 | | 4=16-n | | 4(2x+4)-13= | | 5x^3+21x^2-21x+5=0 | | 5(n+8)=10 | | 5x^2-5x-30=30 | | 50t+125=30t+200 | | 5x-x+4x=7-3 | | x+2.75=6 | | 7x-4=6.5 | | 9-6x=4-3x+3x | | 4-2x=14x+15 | | 2t+6=t+8 |